2019
DOI: 10.1002/tal.1593
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design of multiple positioned tuned mass dampers for structures constrained with axial force capacity

Abstract: The stories of structure may have different and limited axial force capacity. In order to passively control the translational movement of structures, a tuned mass damper (TMD) positioned on a story may cause to exceed axial force capacity of a story.The optimum performance is achieved when all additional masses are positioned on the top story. Whereas, the top stories of structure may be constructed with lower axial force capacity than the lower stories. In that case, the maximum allowed TMD mass for upper sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…where R mfd and R RMS denote, respectively, the reduction of the maximum floor displacement and the reduction of the maximum RMS displacement defined according to Equations ( 25) and (26). In addition, the counter i in the sum numbers the accelerograms used in the tuning process.…”
Section: Practical Design Recommendationsmentioning
confidence: 99%
“…where R mfd and R RMS denote, respectively, the reduction of the maximum floor displacement and the reduction of the maximum RMS displacement defined according to Equations ( 25) and (26). In addition, the counter i in the sum numbers the accelerograms used in the tuning process.…”
Section: Practical Design Recommendationsmentioning
confidence: 99%
“…Keshtegar and Etedali [34] suggested a method based on the dynamic parameters of the structure for the optimal design of mass dampers, which output more accurately than other algorithms. Nigdeli and Bekdaş [35] in their research examined several dampers on the structural floors. ey concluded that the application of the damper at several points in the structure has a more favorable effect than the placement of a damper on the roof of a building.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An optimum design of post-tensioned axially symmetric cylindrical reinforced concrete walls using the harmony search algorithm [10] and novel hybrid metaheuristic methods (Jaya using Lévy flights, Jaya using Lévy flights with probabilistic student phase (JALS), JA using Lévy Flights with consequent student phase (JALS2)), with different height and load cases [11], and the design of cantilever soldier pile retaining walls via the harmony search algorithm [12], are some examples of the use of such algorithms in thin-wall and cantilever retaining wall structures. Optimum parameters of a tuned mass damper for seismically excited structures are determined using several metaheuristic algorithms such as the ant colony optimization, harmony search algorithm, flower pollination algorithm, and bat algorithm [13][14][15][16]. The widespread use of metaheuristic algorithms is proposed not only in passively controlled structures, but also in actively controlled structures (determination of parameters of the Proportional-Derivative-Integral (PID) type controllers using teaching-learning-based optimization [17,18] and harmony search [19]).…”
Section: Introductionmentioning
confidence: 99%